Localization of acetylcholine receptors and synaptic ultrastructure at nerve-muscle contacts in culture: dependence on nerve type - Cohen, MW (The Rockefeller University Press, 1980)
In cultures of xenopus myotomal muscle cells and spinal cord (SC) some of the nerve-muscle contacts exhibit a high density of acetylcholine receptors (AchRs [Anderson et al., 1977, J. Physiol. (Lond.). 268:731- 756,757-773]) and synaptic ultrastructure (Weldon and Cohen, 1979, J. Neurocytol. 8:239-259). We have examined whether similarly specialized contacts are established when the muscle cells are cultured with explants of xenopus dorsal root ganglia (DRG) or sympathetic ganglia (SG). The outgrowth from the ganglionic explants contained neuronal and non- neuronal cell processes. Although both types of processes approached within 100 A of muscle cells, synaptic ultrastructure was rarely observed at these contacts. Because patches of postsynaptic ultrastructure also develop on noncontacted muscle cells, the very few examples of contacts with such specializations probably occurred by chance. AChRs were stained with fluroscent α-bungarotoxin. More than 70 percent of the SC-contacted muscle cells exhibited a high receptor density along the path of contact. The corresponding values for DRG- and SG- contacted muscle cells were 10 and 6 percent. Similar values were obtained when the ganlionic and SC explants were cultured together in the same chamber. The few examples of high receptor density at ganglionic-muscle contacts resembled the characteristic receptor patches of noncontacted muscle cells rather than the narrow bands of high receptor density seen at SC-muscle contacts. In addition, more than 90 percent of these ganglionic- contacted muscle cells had receptor patches elsewhere, compared to less than 40 percent for the SC-contacted muscle cells. These findings indicate that the SC neurites possess a specific property which is important for the establishment of synaptically specialized contacts with muscle and that this property is lacking in the DRG and SG neurites.